Assessment of target and usefulness of complex cyber-physical systems. (22nd December 2021) - Korshunov, Gennady; Varzhapetyan, Artemy; Petrushevskaya, Anastasia; Polyakov, Sergey
Tasks of target management and ensuring efficiency of cyber-physical systems are considered. Features of cyber-physical systems as the main tool of digitalisation are singled out. Approaches to formulating goals based on preservation laws and technical requirements are given. Approaches to management of utility and quality of cyber-physical systems at life cycle stages are considered. Examples of assessment of the target purpose of systems for minimisation of harmful emissions, protection of pipelines from corrosion, systems with implementation of technological innovations are given. The problems for the development of the proposed approaches are formulated.